Amide and ester derivatives of chlorido[4-carboxy-1, 2-disalicylideneaminobenzene]iron(iii) as necroptosis and ferroptosis inducers. Issue 20 (7th May 2020) - Baecker, Daniel; Ma, Benjamin N.; Sagasser, Jessica; Schultz, Lukas; Hörschläger, Carina; Weinreich, Maria; Steiner, Lucy; Kircher, Brigitte; Gust, Ronald
Abstract : Amide and ester derivatives of chlorido[4-carboxy-1, 2-disalicylideneaminobenzene]iron(iii ) were synthesized and characterized as necroptosis and ferroptosis inducers using the acute myeloid leukemia cell line HL-60. Abstract : In continuation of the structure-activity study about 4-substituted chlorido[ N, N ′-disalicylidene-1, 2-phenylenediamine]iron(iii ) complexes as necroptosis and ferroptosis inducers, we introduced a 4-COOH group at the 1, 2-phenylenediamine moiety of the lead ([Fe(iii )salopheneCl]) and derived the resulting complex 15 to the respective ethyl, propyl, or butyl amides (16–18 ) and esters (19–21 ). The compounds 16–21 exerted concentration-dependent antiproliferative and antimetabolic effects against HL-60 cells. The esters were more active than the analogous amides. Elongation of the alkyl chain enhanced the activity of the amides, while that of the esters decreased. The complexes 16–21 induced necroptosis and/or ferroptosis but not apoptosis. Studies on protein binding and uptake into HL-60 cells indicated that the complexes mainly accumulated by passive transport. The high binding tendency of all complexes to apo-Transferrin, however, points to participation of a carrier-mediated transport into the cells, too.